Hydrogel-based cardiac patches for myocardial infarction therapy: Recent advances and challenges - Zhenqiu Liu; Zhi Zheng; Jiahao Xie; Hua Wei; Cui-Yun Yu (Materials Today Bio)
Myocardial infarction (MI) remains the leading cause of death related to cardiovascular diseases globally, presenting a significant clinical challenge due to the specificity of the lesion site and the limited proliferative capacity of cardiomyocytes (CMs) for repairing the infarcted myocardium. Extensive studies reported so far has focused on the utilization of hydrogel-based cardiac patches for MI treatment, highlighting their promising mechanical properties, conductivity, and ability to remodel the microenvironment post-repair. However, the majority of developed cardiac patches have been limited to the myocardial tissue surface via suturing or adhesive administration. Suturing inevitably leads to additional damage to the fragile myocardium, while uneven application of adhesives may result in patch displacement and compromised drug release. Based on these critical issues, we systematically summarize the advantages and drawbacks of using hydrogel patches for MI treatment with emphasis on elucidating various design strategies. Specifically, we first describe the changes in the pathological microenvironment following MI. Next, we discuss the biomimetic types of hydrogel patches, their functional design, and corresponding strategies for microenvironment adaptation, emphasizing adhesion mechanisms, wet adhesion design strategies, and fabrication techniques for hydrogel patches. Finally, we address the potential challenges and prospects of hydrogels as patches for MI therapy. The review is believed to provide theoretical guidance for the development of new therapeutic strategies for effectively MI treatment.